The influence of actors on the content and execution of a bereavement programme: a Bourdieu-inspired ethnographical field study in Sweden - Karidar, Hakima; Lundqvist, Pia; Glasdam, Stinne (Frontiers in Public Health, 2024)
The death of a parent can have profound negative impacts on children, and a lack of adequate support can exacerbate negative life experiences. The study aimed to explore the influences of various actors on the content and execution of a bereavement programme within a Swedish context, taking into account relational and contextual perspectives. The ethnographic field study involved six children, their parents, and eight volunteers. Employing a theory-inspired thematic analysis using Bourdieu’s concepts of position, power, and capital, the empirical material showed that confidentiality undertaken was an essential element in the programme, however, the premisses varied depending on actors’ positions. Volunteers and researchers had different outlets to express their experiences in the program. The programme offered the children an exclusive space for talking about and sharing experiences and feelings. Simultaneously, the programme restricted the children by not allowing them to share their experiences and feelings outside the physical space. The physical settings shaped the different conditions for interactions among the participants. The sessions adopted loss-oriented approaches, where communication between volunteers and children was guided by the volunteers. However, children created strategies for additional, voiceless communication with their peers or themselves. During breaks and mingles, shared interests or spaces connected children (and adults) more than their common experience of parental bereavement.